Pendekatan Wilayah Dalam Studi Islam (Perkembangan Kehidupan Keagamaan dan Aktivitas Muamalah Masyarakat Minoritas Muslim di Asia Tenggara) - Evan Hamzah Muchtar (STAI Asy-Syukriyyah, 2019)
This paper will discuss Islamic studies on religious life and muamalah activities with regional approaches in Southeast Asia, especially in Muslim minority communities in Myanmar, Thailand and the Philippines. The discussion begins with the understanding of Islamic studies, the background of the spread of Islam in Southeast Asia, and the development of muamalah Muslim minority communities in Southeast Asia, especially in Myanmar, Thailand and the Philippines. Their position as a minority influences the development of religious institutions. In the process of national integration launched by the government, Muslim communities face changes in social and political orientation.